2023
DOI: 10.21203/rs.3.rs-2459856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated Interleukin (IL)-6 as a Predictor of Disease Severity among Covid-19 Patients: a prospective cohort study

Abstract: Background accompanied to the spreading of coronavirus disease 2019 (Covid-19) in the world, identifying factors related to the severity of the disease is one of the interests of physician and medical researchers. We hypothesized that interleukin 6 serum level is associated with severe outcome. Methods In this longitudinal prospective cohort study we enrolled 208 confirmed COVID-19 patients who were admitted to the Tohid Hospital (Sanandaj, Iran). Patients were classified into two groups based on IL-6 value … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Furthermore, IL-6 levels were found to be substantially related to various clinical and laboratory indicators predicting a systemic infammatory response, such as CRP, ferritin, D-dimer, and LDH (Table S3). Te same correlation was reported by other studies; however, IL-6 seemed to be the major prognostic efector [24,47].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, IL-6 levels were found to be substantially related to various clinical and laboratory indicators predicting a systemic infammatory response, such as CRP, ferritin, D-dimer, and LDH (Table S3). Te same correlation was reported by other studies; however, IL-6 seemed to be the major prognostic efector [24,47].…”
Section: Discussionsupporting
confidence: 90%
“…COVID-19 susceptibility and severity among studied cases were linked to age and associated comorbidities. Nikkhoo et al documented the same fnding [24,25].…”
Section: Discussionmentioning
confidence: 78%
“…Cytokine levels are commonly assessed in the blood to determine systemic levels of inflammation. Prior studies, including one from this cohort 14 , have shown elevated systemic levels of specific cytokines, including IL-1Ra and IL-8, have been previously associated with an increased risk of severe disease and poor outcomes in persons with SARS-CoV-2 infection [15][16][17][18] . However, little is known about the mucosal immune response to SARS-CoV-2 infection and whether the mucosal immune responses correlate with systemic immune responses, especially at later time points.…”
Section: Cytokine and Chemokine Responses Are Distinct Between Nasal ...mentioning
confidence: 87%
“…Cytokine storm, the uncontrolled release of proinflammatory mediators are major risk factors for COVID‐19 severity. Among the cytokines, interleukin 6 (IL‐6) is one of the key cytokines 9,10 and there are some evidence that blood IL‐6 level is positively correlated to disease severity in COVID‐19 patients with severe complications 11,12 . To guide the local health authorities and predict the future severity of the disease, the primary objective of this study was firstly to measure the levels of IL‐6 in case and control groups as well as in relation to demographic factors, and secondly to determine the relationship between IL‐6 levels with the percentage of lung involvement.…”
Section: Introductionmentioning
confidence: 99%